Perbandingan Ekonomis Pengadaan Alat Berat Sistem Sewa dan Beli dalam Pekerjaan Konstruksi - Ida Farida; Nova Audi Ireland (Institut Teknologi Garut, 2026)
One of the supporting factors for construction development work to be able to shorten the time, simplify, and control the quality of work is the need for heavy equipment. This study aims to compare the cost of procuring heavy equipment between buying or renting heavy equipment for the Ciplaz Garut construction project, in order to determine a more efficient alternative. The method used is financial analysis with Net Present Value (NPV) to measure the difference between investment and future net cash receipts, and the Internal Rate Of Return (IRR) method to analyze the rate of return on capital. The analysis results show that with a project duration of 2 years, the NPV for buying heavy equipment is -Rp. 5,845,078,344 (negative), while the NPV for renting heavy equipment is Rp. 959,780,692 (positive). In addition, the IRR for buying heavy equipment is 0 percent (less than MARR 4.25 percent), while the IRR for renting heavy equipment is 20.47 percent (greater than MARR 4.25 percent). Based on the results of the analysis that has been carried out, the procurement of heavy equipment with a rental system is more profitable to do than the procurement of a heavy equipment purchase system.